A fully integrated graphene-polymer field-effect transistor biosensing device for on-site detection of glucose in human urine. (March 2022) - Huang, C.; Hao, Z.; Wang, Z.; Zhao, X.; Wang, H.; Li, F.; Liu, S.; Pan, Y.
Abstract: Convenient and rapid self-measurement of the glucose level in the body is of great significance for diabetics to know their health conditions in time. In view of this, a polymer functionalized graphene field-effect transistor (P-GFET) portable biosensing device is demonstrated for glucose monitoring. The polymer is synthesized by acrylamide/3-acrylamidophenylboronic acid (AAPBA)/N, N-dimethylaminopropyl acrylamide. In the presence of glucose, the P-GFET shows Dirac point shifts and current changes as a result of the covalent bond between glucose and AAPBA in the synthesized polymer on graphene. The sensitivity of this P-GFET sensor can increase while the density of AAPBA in polymer increases. The used sensor could regain the detection capability after hydrochloric acid treatment due to the reversible reaction between polymer and glucose. In addition, the chemisorption interaction between polymer and glucose, which is stronger than physisorption interaction with other objects in urine, has been supported by the density functional theory study. The P-GFET shows high sensitivity of 822 μA∗cm −2 ∗mM −1 with a limit of detection of 1.9 μM during human urine glucose monitoring. The sensor holds a detection range of 0.04–10 mM and good reusability over 20 times. With the customized portable real-time measurement capability in urine, our P-GFET sensor can offer advantages over current glucose detection methods. Graphical abstract: Image 1 Highlights: A fully integrated and portable nanosensing system for glucose detection in urine. The sensor has reusability and high sensitivity due to the polymer functionalization. The composition and ratio of the polymer indicate vital factors of the sensor' performance.